“En komponerende Dame”. Modtagelsen af Nancy Dalbergs musik i samtiden - Jensen, Lisbeth Ahlgren (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
The article takes the form of an examination of the newspaper reviews of the first performances of Nancy Dalberg’s compositions in the years 1915 to 1937. In doing so, the aim was to find out why on the one hand she was considered one of her time’s foremost female composers but on the other hand has almost completely vanished from view in subsequent musical life. Newspaper reviewers generally devoted her great attention and in the beginning offered constructive criticism, considering her both talented and skilled in composition. But when in 1918 she offered herself as a symphonic composer, the critical tone became sharper, even though there was amazement that a woman should try her strength with such a prestigious musical genre as the symphony. However, lack of performance opportunities meant that she ceased to express herself in large-scale orchestral works but concentrated on composing chamber music and songs. The criticism of the songs in particular reveals an expectation that as a woman she should be expressing herself in a particularly feminine musical language, with an emphasis on the emotional and singable, but as she did nothing to meet these expectations, she was subjected to a rough ride. Close reading of newspaper critics shows that it was acceptable in society for a woman to manifest herself as an artist but that she was expected to express herself in a particular way which would not assail the prevailing conception of femininity. In other words, music criticism was characterised by a sexual ideology which prevented it from evaluating Nancy Dalberg’s compositions objectively. As a result her creative efforts were not taken seriously and gradually she lost the confidence to present herself as a composer. Apparently value-neutral criticism thus proves to be both a communicator of sexual ideology and responsible for maintaining a particular view of women artists.